Investigation of CO2 hydrate growth kinetics in gas-dominated systems - Changjun LI; Sen DONG; Wenlong JIA; Fan YANG; Qian GAO; Jiankun YANG (You-qi chuyun, 2025)
ObjectiveCO2 is prone to form hydrates when in contact with liquid water under low-temperature, high-pressure conditions, impacting the safe operation of pipelines. Thus, it is essential to enhance the understanding of CO2 hydrate growth characteristics in gas-dominated systems within pipelines, elucidate the growth kinetics of these hydrates, and establish a theoretical framework for predicting and preventing hydrate formation in CO2 transmission pipelines. MethodsA high-pressure, low-temperature multiphase flow loop test device was employed to conduct 16 groups of tests on CO2 hydrate growth and decomposition under conditions of 4.00–4.50 MPa pressure, 1.0–3.0 ℃ ambient temperature, 2.20 m/s flow rate, and 4％ water content. The growth and decomposition kinetics of hydrates in gas-dominated systems at low flow rates and low water content were analyzed, along with the adhesion mechanism during formation and factors influencing the growth rate of CO2 hydrates. Additionally, a correlation equation for the proportionality factor u, related to system temperature and pressure, was proposed based on the Turner kinetic model to enhance the understanding of mass transfer and supercooling effects on CO2 hydrate growth rates, thereby refining the basic Turner kinetic model. ResultsThe kinetics of CO2 hydrate growth and decomposition were observed in four distinct stages: induction, rapid growth, slow growth, and decomposition. The induction time decreased with increasing initial pressure and increased with higher ambient temperatures. Low temperatures and liquid accumulation on the pipe wall were essential for hydrate growth under low flow rate conditions, with mass transfer identified as a primary control mechanism. The growth rate was influenced by system temperature and pressure; higher pressures and lower temperatures resulted in faster growth rates. ConclusionThe average relative error of the modified model in predicting hydrate growth rates decreased from 82.55％ to 10.74％, significantly enhancing the accuracy of predictions in gas-dominated systems under low flow rates.